2014
DOI: 10.1681/asn.2013060640
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic MicroRNA-126 Protects against Renal Ischemia/Reperfusion Injury by Promoting Vascular Integrity

Abstract: Ischemia/reperfusion injury (IRI) is a central phenomenon in kidney transplantation and AKI. Integrity of the renal peritubular capillary network is an important limiting factor in the recovery from IRI. facilitates vascular regeneration by functioning as an angiomiR and by modulating mobilization of hematopoietic stem/progenitor cells. We hypothesized that overexpression of miR-126 in the hematopoietic compartment could protect the kidney against IRI via preservation of microvascular integrity. Here, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 66 publications
(69 reference statements)
3
76
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Several recent studies suggested that restoring the renal microvasculature may provide novel therapeutic options for patients with CKD. [8][9][10][11][12] Thus far, however, quantitative imaging tools allowing for the noninvasive monitoring of morphologic and functional alterations of the renal microvasculature during disease progression have been lacking, and studies investigating vessel rarefaction in CKD have been largely restricted to invasive microscopic end-point analyses. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] We here employed in vivo and ex vivo mCT-based imaging techniques, alongside conventional immunohistochemical methodologies, to demonstrate that (1) contrast-enhanced in vivo mCT imaging is highly suitable for accurate and noninvasive monitoring of vessel functionality during progressive kidney diseases, via quantifying the renal rBV; (2) the renal rBV continuously decreases during early-to-late-stage renal disease progression; (3) vessel functionality is reduced immediately after renal injury prior to the onset of interstitial fibrosis, supporting the assumption that endothelial injury might be a major initiating cause of fibrosis development; and (4) in addition to peritubular capillaries, arterial vessels of virtually all calibers undergo substantial alterations during progressive renal disease with regard to vessel branching, size, and tortuosity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Several recent studies suggested that restoring the renal microvasculature may provide novel therapeutic options for patients with CKD. [8][9][10][11][12] Thus far, however, quantitative imaging tools allowing for the noninvasive monitoring of morphologic and functional alterations of the renal microvasculature during disease progression have been lacking, and studies investigating vessel rarefaction in CKD have been largely restricted to invasive microscopic end-point analyses. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] We here employed in vivo and ex vivo mCT-based imaging techniques, alongside conventional immunohistochemical methodologies, to demonstrate that (1) contrast-enhanced in vivo mCT imaging is highly suitable for accurate and noninvasive monitoring of vessel functionality during progressive kidney diseases, via quantifying the renal rBV; (2) the renal rBV continuously decreases during early-to-late-stage renal disease progression; (3) vessel functionality is reduced immediately after renal injury prior to the onset of interstitial fibrosis, supporting the assumption that endothelial injury might be a major initiating cause of fibrosis development; and (4) in addition to peritubular capillaries, arterial vessels of virtually all calibers undergo substantial alterations during progressive renal disease with regard to vessel branching, size, and tortuosity.…”
Section: Discussionmentioning
confidence: 99%
“…Bijkerk et al (14) showed that overexpression of miR-126 in the hematopoietic compartment can protect the kidney via preservation of microvascular integrity during ischemic renal injury and supports recovery by promoting vasculogenic progenitor cell mobilization. In another study (2), miR-127 was identified as a renoprotective miRNA during ischemic renal injury.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Apart from proangiogenic growth factors (150), several proteins have been suggested to play a role in endothelial cell remodeling leading to fibrosis including ephrin-B (208), Crim-1 (209), Id proteins (210), miR-126 (211), and the glycocalyx of glomerular endothelial cells (212). In renal transplantation, peritubular endothelial damage, in particular endothelial C4d staining, reflects rejection (213).…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%